2015
DOI: 10.4049/jimmunol.1401941
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of the Transcription Factor ARID3a in Lupus Patient Hematopoietic Progenitor Cells

Abstract: Although hematopoietic progenitor/stem cells (HPSCs) are used for transplantation, characterization of the multiple subsets within this population in man has lagged behind similar studies in mice. We found that expression of the DNA-binding protein, ARID3a, in mouse stem cells was important for normal development of hematopoietic lineages; however, progenitors expressing ARID3a in man have not been defined. We previously showed increased numbers of ARID3a+ B cells in nearly half of systemic lupus erythematosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 60 publications
(75 reference statements)
1
29
0
Order By: Relevance
“…We previously showed that ARID3a was differentially expressed in multiple subsets of adult peripheral blood HSPCs in lupus patients versus healthy controls (16). To better define the normal roles for ARID3a in early hematopoiesis, we assessed expression in multiple hematopoietic subsets of lineage negative, CD34+ cord blood HSPCS as defined by Notta et.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that ARID3a was differentially expressed in multiple subsets of adult peripheral blood HSPCs in lupus patients versus healthy controls (16). To better define the normal roles for ARID3a in early hematopoiesis, we assessed expression in multiple hematopoietic subsets of lineage negative, CD34+ cord blood HSPCS as defined by Notta et.…”
Section: Resultsmentioning
confidence: 99%
“…Using flow cytometry, HSPCs were gated to allow identification of hematopoietic stem cells (HSCs), multi-myeloid progenitors (MMPs), multi-potent progenitors (MPP), and multi-lymphoid progenitors (MLP) (Fig. 1A) (16). Analysis of these subsets for numbers of ARID3a + cells revealed that 74% of HSCs and MMPs expressed ARID3a, while only 43% of MLPs and 20% of MPPs were ARID3a positive (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations